Financial Analysis of Rain Water Harvesting Tools in Pamor Hamlet, Banjardowo Village, Kradenan Sub District, Grobogan District - Nur Ainun Jariyah; Purwanto (Jurnal Penelitian Kehutanan Wallacea, 2019)
The drought that occurs in the dry season is one of the hydrometeorological disasters. A total of 82 villages of 12 districts in Grobogan, Central Java, experience a clean water crisis due to drought because the well, as their main source of water, is likely to go dry. Therefore, a solution is needed to anticipate the water shortage. The aims of this paper is to analyze financially the water harvesting building which can be used as a reference for the community. The research was conducted in Pamor Hamlet, Banjardowo Village, Kradenan District, Grobogan Regency. The method used was to build the rainwater harvesting engineering models, namely (a) recycling tools for washing and bathing, (b) dirt filter wells, (c) three meters depth infiltration wells (1 well and 2 wells), and (d) five meters deep infiltration wells (1 well and 2 wells). Data collection was done by conducting a survey of the community. The data collected were the costs required for the construction of the rainwater harvesting equipment, maintenance, electricity, supporting materials, etc. The income was approached with replacement costs if the community buys water during the dry season. The financial analyses of NPV, IRR, BCR, and PP were employed. The results showed several feasible models to be applied, namely recycling equipment for washing and bathing, dirt filtering equipment, three meters deep infiltration wells (1 piece) and a depth of 5 meters (1 piece). This model is very good to be adopted by the community because it is easy and has minimal costs.